PENGUNGKAPAN MODAL INTELEKTUAL DAN KEUANGAN DALAM KAPITALISASI PASAR DENGAN SIKLUS HIDUP INDUSTRI SEBAGAI PEMODERASI (INTELLECTUAL CAPITAL DISCLOSURE AND FINANCIAL DISCLOSURE IN MARKET CAPITALIZATION WITH INDUSTRY LIFE CYCLE AS MODERATING VARIABLE) - Azis, Siti Nafisah; Pagalung, Gagaring; Habbe, Abdul Hamid (UI Scholars Hub, 2019)
Previous research has not examined which of intellectual capital disclosure and financial disclosure contains more relevant information in investor decision making in industry life cycle perspective. This research examines the effect of industry life cycle in moderating the relationship between intellectual capital disclosure, financial disclosure, and market capitalization; the influence of intellectual capital and financial disclosure on market capitalization; and the influence of good corporate governance on intellectual capital and financial disclosure. The research sample was all non-financial companies listed in the Indonesian Stock Exchange in 2014-2015. By using multiple linear regression, the research finds that industry life cycle moderates the relationship between intellectual capital disclosure and market capitalization, however, it does not moderate the relationship between financial disclosure and market capitalization. Intellectual capital disclosure has a positive effect on market capitalization, whereas financial disclosure does not influence market capitalization. Good corporate governance has a positive effect on intellectual capital and financial disclosure. This study provides a new evidence that the disclosure of relevant information based on industry life cycle will be realized with the implementation of optimal good corporate governance. The information produced can provide a signal that influences investor decisions.